Comparative vocational education research : enduring challenges and new ways forward - Pilz, Matthias [Herausgeber]; Li, Junmin [Herausgeber] (Springer VS, 2020)
"The volume is devoted to the research of comparative vocational education and training, placing a special emphasis not only on theoretical development, but also on methodological approaches and on achieving excellent research outcomes by strictly concerning comparative studies in vocational education and training. This volume contains scientific contributions by renowned researchers of vocational education from all over the world." (Publisher, BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; T 3 Forschungsmethoden; T 2.1 Bildungstheorien; Vergleichende Berufsbildungsforschung; Internationaler Vergleich; Methodologie; Berufsbildungstheorie; Praxisforschung